2014
DOI: 10.15277/bjdvd.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonists in type 2 diabetes - NICE guidelines versus clinical practice

Abstract: Injectable glucagon-like peptide-1 receptor agonists (GLP1ras) have the distinct advantage of promoting weight loss as well as lowering glucose in type 2 diabetes. Treatment with a GLP-1ra is costly, thereby necessitating a restriction on widespread use, thus in the UK the National Institute for Health and Care Excellence (NICE) has published guidance on the use of these drugs.In the UK the Association of British Clinical Diabetologists (ABCD) conducted two nationwide audits on the use of exenatide twice daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…The advice to use the least expensive option at first appears sensible, but evidence is emerging that there are clinically important differences between the shorter and longer duration agents. 15,16 Customising GLP-1ra to patients' needs may be an important part of their effective and safe use in therapy. Advising the use of GLP-1ra (or DPP-4 inhibitors) with the lowest acquisition costs might also be problematic given the more limited licence, differences in recommendations in patients with renal impairment and the much smaller worldwide clinical experience when compared with more expensive agents from the same class.…”
Section: Incretin-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The advice to use the least expensive option at first appears sensible, but evidence is emerging that there are clinically important differences between the shorter and longer duration agents. 15,16 Customising GLP-1ra to patients' needs may be an important part of their effective and safe use in therapy. Advising the use of GLP-1ra (or DPP-4 inhibitors) with the lowest acquisition costs might also be problematic given the more limited licence, differences in recommendations in patients with renal impairment and the much smaller worldwide clinical experience when compared with more expensive agents from the same class.…”
Section: Incretin-based Therapiesmentioning
confidence: 99%
“…Common sense supports reviewing the efficacy of these relatively expensive treatments, but with a balanced approach. 16 We also take issue with the recommendation that GLP-1ra/insulin combinations can only be commenced within specialist care. This combination is much easier to use than insulin intensification regimes, which many GPs undertake frequently.…”
Section: Incretin-based Therapiesmentioning
confidence: 99%
“…57 It was found that GLP-1RA treatments were more effective in non-insulin treated patients than in insulin treated patients. 82 Although approximately 60% of the patients in both audits achieved reductions in both HbA1c and weight, only 25% in the liraglutide audit and 29% in the EBID audit met the NICE criteria of HbA1c reduction ≥1% and weight reduction >3% to continue GLP-1 treatment. 82 GI side effects were reported to be higher with EBID (24%) than with liraglutide (16%).…”
Section: Real Life Clinical Experience Of Glp-1 Use In the Ukmentioning
confidence: 98%
“…82 Although approximately 60% of the patients in both audits achieved reductions in both HbA1c and weight, only 25% in the liraglutide audit and 29% in the EBID audit met the NICE criteria of HbA1c reduction ≥1% and weight reduction >3% to continue GLP-1 treatment. 82 GI side effects were reported to be higher with EBID (24%) than with liraglutide (16%). 81 Both EBID and liraglutide treatment were associated with a reduction in SBP, total cholesterol and triglycerides.…”
Section: Real Life Clinical Experience Of Glp-1 Use In the Ukmentioning
confidence: 98%
See 1 more Smart Citation